Greek doctors facing cholera: from miasmas to bacteries - Barlagiannis, Athanasios (Neusis, 2024)
The article provides an overview of 19th-century Greek medical literature related to cholera. Ιt analyzes fifteen studies (articles and monographs) published between 1815 and 1915 and studies the schemes developed to explain the genesis and spread of cholera. Although it tries to fit these schemes into the three general explanatory theories of contagion, miasma and bacteriology, it avoids strict typology by demonstrating the exchanges that took place between the theories as well as the internal differences that developed within each of the three, both among authors of the same era and within time. Finally, it tries to situate the ideas of the Greek doctors within the influences they received from their Western European counterparts.